Práticas de letramento acadêmico em um curso de graduação em fonoaudiologia: um estudo de caso - Luciana Mariz (2021)
This research examines ways in which Speech Therapy undergraduate students use writing and analyze meanings attributed to literacy as they engage in academic literacy practices. To do so I adopted an ethnographic perspective and a literacy as social practice approach to analyze literacy events constructed by research participants. The study was guided by theoretical and methodological principles anchored in the discussions proposed by the New Literacy Studies (NLS) (BARTON; HAMILTON, 2000; GEE, 1990; STREET, 1984-1995, 2013, 2014), by the academic literacies approach (LEA; STREET, 1998, 2014; STREET, 2010), by the dialogic-responsive perspective of the Bakhtin Circle (BAKHTIN; VOLOCHÍNOV, 1929- 2004; BAHKTIN, 1979-2003). The research logic, built from an ethnographic perspective (CASTANHEIRA et al. 2001; GREEN; DIXON; ZAHARLICK, 2005; HEATH; STREET, 2008). Data construction was carried out by the developing participant observation during 18 months at the at the Faculty of Medicine resulting in data set that includes field notes, audio and video records of interviews, and meetings with teachers, meetings of a Mentorship Program and classes in a course on reading and writing academic texts that was taught by me. The identification and examination of rich points (AGAR, 1999, 2006) from an ethnographic perspective allowed me to develop a culturally sensitive perspective to the literacy practices in which the participants were involved. The analysis made visible how teacher took responsive actions to support students in facing academic challenges in a multidisciplinary undergraduate course. Analysis of Mentorship Program meetings made visible how undergraduates are encouraged to assume an entrepreneurial identity in the management of their time and own knowledge and in the construction of a network of contacts, aiming at a future insertion in the job market. A reflexive analysis of classes on reading and writing academic texts, taught by me, showed a mismatch between the academic literacies approached I had adopted and students demands and expectations aligned with the skills models and the socialization model (LEA; STREET, 1998, 2014; STREET, 2010). Finally, the analysis demonstrated the dynamics and complexity of the uses that are made of language in the context investigated in relation to academic literacies.